ParaNorman - Butler, Chris, 1974-; Fell, Sam.; Goodman, John, 1952-; Mann, Leslie, 1972-; Affleck, Casey, 1975-; Mintz-Plasse, Christopher, 1989-; Kendrick, Anna.; Smit-McPhee, Kodi.; LAIKA (Firm); Focus Features; Universal Studios Home Entertainment (Firm) ([United States] : Universal Studios Home Entertainment, 2012)
From the makers of Coraline comes the story of Norman, a boy who must use his special powers to save his town from a centuries-old curse. In addition to spooky zombies, he'll also have to take on unpredictable ghosts, wily witches, and, worst of all, clueless grown-ups. But this young ghoul whisperer will soon find his paranormal activities pushed to their otherworldly limits.
Title from sell sheet.
Release date: Nov. 27, 2012.
Special features: preliminary animatic sequences; 7 featurettes on the making of ParaNorman; "Peering through the veil: go behind the scenes to see how this stunning stop-motion animation was created" featurette; feature commentary with writer/director Chris Butler and director Sam Fell.
Director of photography, Tristan Oliver; music, Jon Brion; editor, Christopher Murrie; lead animators, Travis Knight, Jeff Riley, Payton Curtis.
John Goodman, Leslie Mann, Casey Affleck, Christopher Mintz-Plasse, Anna Kendrick, Kodi Smit-McPhee.
MPAA Rating: PG.
Keywords: Zombies -- Juvenile films; Ghosts -- Juvenile films; Supernatural -- Juvenile films; Fiction films; Animated films; Feature films; Fiction films; Children's films; Video recordings for the hearing impaired